Penanganan Bronkitis Kronis Disertai Skabiosis dan Infestasi Kutu pada Kucing Domestik - Vonny, Ni Ketut; Putriningsih, Putu Ayu Sisyawati; Widyastuti, Sri Kayati (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
Chronic bronchitis is common in cats, characterized by chronic neutrophilic inflammation of the bronchi and coughing and sneezing for more than two months. Cats can also be infected with ectoparasites such as fleas and mites. This article aims to provide information on the management of chronic bronchitis with symptomatic therapy through nebulization. A 1-year-old male domestic cat, weighing 2.15 kg, presented with a 3-month history of sneezing with mucopurulent nasal discharge, stridor, dry rales, and erythematous lesions, crusting, and alopecia on the ears. Hematologic examination indicated leukocytosis, lymphocytosis, and thrombocytopenia. A chest radiograph revealed a bronchial pattern and cytology of the nasal discharge revealed coccobacillus bacteria. Deep skin scrapings and flea combing identified Notoedres sp. and Felicola subrostratus. The cat was diagnosed with chronic bronchitis with scabies and fleas, with a favorable prognosis. Oral therapy with amoxiclav and methylprednisolone, and inhaled salbutamol. Spot-on therapy with fipronil and (s)-metophrene and 6% sulfur for ectoparasites, as well as Livron B-Plex® and fish oil. On the fourteenth day, clinical and laboratory evaluations showed recovery, while platelet counts returned to normal thirty days after therapy. Cats should be monitored regularly, their vitamin and mineral needs met, and vaccinations administered.